Cover Feature: The Fast and the Capacious: A [Ni(Salen)]‐TEMPO Redox‐Conducting Polymer for Organic Batteries (Batteries & Supercaps 2/2021). Issue 2 (18th January 2021) - Vereshchagin, Anatoliy A.; Lukyanov, Daniil A.; Kulikov, Ilia R.; Panjwani, Naitik A.; Alekseeva, Elena A.; Behrends, Jan; Levin, Oleg V.
Abstract : The Cover Feature illustrates the structure of a novel redox‐conducting polymer for energy‐storage applications. The material combines redox‐active nitroxyl radicals (depicted as bright green spheres) and a conductive Salen‐type backbone (shown as Ni‐containing complexes). The synthetic approach provides the possibility of combining the high charge/discharge speed of batteries and the significantly improved capacity of the hybrid material. More information can be found in the Article by O. V. Levin and co‐workers .